Effectiveness of Web search Engines Using a Query Sample in the Field of Technology - Sabha Ali, Sumeer Gul, (IJoLIS, 2024)
Purpose- The aims to provide a systematic evaluation of the select search engines on the basis of two information retrieval paramaeters,precision and recall.